Skype video responsiveness to bandwidth variations - Luca De Cicco; Saverio Mascolo; Vittorio Palmisano (Proceedings of the 18th International Workshop on Network and Operating Systems Support for Digital Audio and Video, 2008)
The TCP/IP stack has been extremely successful for reliable delivery of best-effort, time insensitive elastic type data traffic. Nowadays, the Internet is rapidly evolving to become an equally efficient platform for multimedia content delivery. Key examples of this evolution are, to name few, YouTube, Skype Audio/Video, IPTV, P2P video distribution such as Coolstreaming or Joost. While YouTube streams videos using the Transmission Control Protocol (TCP), applications that are time-sensitive such as Skype VoIP or Video Conferencing employ the UDP because they can tolerate small loss percentages but not delays due to TCP recovery of losses via retransmissions. Since the UDP does not implement congestion control, these applications must implement those functionalities at the application layer in order to avoid congestion and preserve network stability. In this paper we investigate Skype Video in order to discover to what extent this application is able to throttle its sending rate to match the unpredictable Internet bandwidth while preserving resource for co-existing best-effort TCP traffic.
Keywords: video over IP; Congestion control; Skype